Adults with pertussis - Maclean, D. W. (1982)
Eighty adults were diagnosed in one general practice as having infection due to Bordetella pertussis, type 1.3, during a period of 30 months. Their clinical presentation and progress is recorded. A plea is made for attention to be paid to this infection in adults.